The Effect of Online-based Emotional Freedom Technique on the Blood Pressure during the Covid-19 Pandemic - Healthy Seventina Sirait; Faridah Mohd Said; Nur Syazana Umar (International Journal of Nursing Information, 2022)
Complications due to hypertension are dangerous. Therefore self-care management is needed. Freedom emotional technique (EFT) therapy is a non-pharmacological treatment that can help change blood pressure. During the Covid-19 pandemic, online EFT is the right solution. This study aims to determine the effect of online-based EFT on blood pressure during the Covid-19 pandemic. This research method uses pre-experimental, namely one group pretest and posttest design. The sample was selected using purposive sampling technique with a total sample of 50 respondents. The research location is Kalimeang village, Karangsembung Sub-district, Cirebon District, Indonesia. The research instruments used were observation sheets, sphygmomanometers, and stethoscopes. The data analysis used the Wilcoxon test. The results of this study indicated that online-based EFT therapy affected the change in blood pressure among patients with hypertension during the covid-19 pandemic. This research contributes to the reference of nursing practice by applying EFT therapy to patients to change their blood pressure with online treatment.